Effectiveness of a brief stress reduction program for health care personnel during the COVID-19 pandemic: A pilot study - Silva-Dominguez, Daniel Sergio (2023)
Objective: To determine the influence of a brief stress reduction program in health workers of the National Maternal and Perinatal Institute during the COVID-19 pandemic. Materials and Methods: This research corresponds to a quasi-experimental study, which consist of the elaboration and application of a brief stress reduction program in workers of the Puericulture area of the INMP. The population consisted of 45 workers, 30 of whom complied with the inclusion criteria for the pilot study, from which a sample of 15 participants was distributed, by convenience, for the experimental group and 15 for the control group. The Depression, Anxiety and Stress Scale (Dass21) was applied at the beginning of the investigation and after concluding the program. The analysis of frequencies and percentages of the variable, analysis of adjusted goodness of fit to the normal curve, and Student's t-tests for correlated samples (p<0.05) pre and post intragroup test with a confidence level of 95% were carried out. Results: Significant differences were found in the experimental group in their pre and post treatment measures respectively in the variables Stress (T=5.20, p<0.001, D=0.742, Mean Dif=3.00); Anxiety (T=3.15, p<0.007, D=0.414, Mean Dif=2.20) and Depression (T=3.97, p<0.001, D=0.426, Mean Dif=3.97) reducing the averages of these variables after the application of the pilot program. Conclusion: The brief program for stress reduction is effective for stress reduction, and due to the fact that in its sessions cognitive behavioral strategies for the improvement of mental health were trained, indicators of anxiety and depression present in the sample were reduced in a secondary way.